Studi Pemanfaatan Limbah Cair Ikan dan Udang sebagai Substrat dalam Produksi Listrik pada Sistem Microbial Fuel Cell (MFC): Study of Utilization of Fishery and Shrimp Wastewater as Substrate in Electricity Production in Microbial Fuel Cell (MFC) System - Alfiah Alif; Muhamad Jalil Baari; Amalyah Febryanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Microbial fuel cell (MFC) is a technology that utilizes bacteria in organic medium that can convert chemical energy into electrical energy. This technology can be used to treat fishery waste and shrimp waste which is rich in organic matter. This study aimed to measure the performance of the MFC system on fishery wastewater and shrimp wastewater as a means of producing bio-electricity while reducing the waste load. This study used different types of electrodes, including zinc, aluminum, copper, and carbon graphite. This technology used 0.2 M KMNO4 electrolyte solution. The research method includes three stages; production of fishery wastewater and shrimp wastewater, assembly of a dual chamber MFC bioreactor, and measurement of waste electrical energy produced. The value of electricity production with the highest average in fishery wastewater was obtained by adding electrolyte solution to the Zn/Cu electrode during 117 hours of observation were 6.86 mA with a potential difference of 1.469 V meanwhile in shrimp wastewater was obtained by adding electrolyte solution to the Al/Cu electrode were 4.38 mA with a potential difference of 1.335 V.This study can be concluded that higher electricity production is obtained from the utilization of fish wastewater using Zn/Cu electrode.